2019
DOI: 10.29252/jafm.12.02.28923
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Analysis of Laminar Forced Convection and Entropy Generation of a Diamond-Fe3O4/Water Hybrid Nanofluid in a Rectangular Minichannel

Abstract: The convective heat transfer and entropy generation of diamond-Fe3O4/water hybrid nanofluid through a rectangular minichannel is numerically investigated under laminar flow conditions. Nanoparticle volume fractions for diamond-Fe3O4/water hybrid nanofluid are in the range 0.05-0.20% and Reynolds number varies from 100 to 1000. The finite volume method is used in the numerical computation. The results obtained for diamond-Fe3O4/water hybrid nanofluid are compared with those of diamond/water and Fe3O4/water conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 36 publications
1
11
0
2
Order By: Relevance
“…To solve equations (11) and (14), the Laplace transform method will be used and closed form solutions will be developed for the velocity and temperature respectively subject to the corresponding initial and boundary conditions from equations (15) to (17).…”
Section: Solution Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…To solve equations (11) and (14), the Laplace transform method will be used and closed form solutions will be developed for the velocity and temperature respectively subject to the corresponding initial and boundary conditions from equations (15) to (17).…”
Section: Solution Of the Problemmentioning
confidence: 99%
“…Applying the Laplace transform to equation (14), keeping in mind the Laplace transform of Caputo-Fabrizio fractional operator defined in equation (8), and using the corresponding initial condition from equation (15) yield the following transformed energy balance:…”
Section: Solutions Of the Temperature Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that injection is a sufficient condition to reduce the skin friction and water is a better coolant than air under the injection process, and they also found that thermal conductivity enhances and the magnetic effect suppresses the skin friction. Following the footsteps of Wang, many researchers enriched the literature by discussing the various physical models in the arena of extending cylinders, such as Mukhopadhyay, 25 Wang, 26 Abbas et al, 27 Uysal et al, 28 and Usman et al 29 The influence of Lorentz force arising due to external applied magnetic field over an extending cylinder was initially analyzed by Ashorynejad et al 30 and was further discussed by Elbashbeshy et al 31 To the authors' best knowledge, no studies have been performed on the hybrid nanofluid movement past a stretching porous cylinder with the effect of radiation, Lorentz force, suction, and variable viscosity. The above-mentioned physical model has many applications in engineering and technology field.…”
Section: Introductionmentioning
confidence: 99%
“…There are among others: power industry (Mikielewicz & Mikielewicz, 2010), space industry (Brutin et al 2013), automotive industry (Sakamatapan & Wongwises, 2014), avionics industry (Najim & Feddaoui, 2018), solar industry (Zhou et al 2017), cryogenic industry (Zhou et al 2014), refrigeration industry (García-Cascales et al 2017), chemical and biological industry (Amador et al 2004). There are also some works that are trying to combine the minichannels with nanofluids (Uysal et al 2019).…”
Section: Introductionmentioning
confidence: 99%